Electrohydrodynamic‐enhanced internal pipe flows from a One‐Dimensional Turbulence perspective - Medina Méndez, Juan A.; Schmidt, Heiko; Bacher, Christian; Riebel, Ulrich (Proceedings in applied mathematics and mechanics, 2021)
The One‐Dimensional Turbulence (ODT) model is applied for the evaluation of internal pipe flows subject to electrohydrodynamic (EHD) forces. The ODT formulation presented here incorporates the effects of the electrostatic potential energy transfer to the kinetic energy of the flow due to EHD instabilities in the presence of a corona discharge. Results for integral quantities such as the skin friction coefficient Cf and the Nusselt number Nu are obtained from ODT simulations and compared to available experimental data [1,2]. The results demonstrate the capabilities of ODT for simulating EHD flows.